2014
DOI: 10.1128/aac.02856-14
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid-Induced Lactic Acidosis in Two Liver Transplant Patients with the Mitochondrial DNA A2706G Polymorphism

Abstract: f Mitochondrial toxicity has been recently suggested to be the underlying mechanism of long-term linezolid-associated toxicity in patients with 16S rRNA genetic polymorphisms. Here, we report for the first time two cases of lactic acidosis due to long-term linezolid exposure in liver transplant recipients who presented an A2706G mitochondrial DNA polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 12 publications
(26 reference statements)
0
6
1
Order By: Relevance
“…Therefore, we suggest lactate monitoring during linezolid therapy within day 7. Elevation of serum lactate was more prevalent in patients with other comorbidities, [ 12 , 13 ] but in our study, such elevation also occurred in patients without comorbidities. Therefore, we suggest lactate monitoring for all patients, and not the at-risk group alone.…”
Section: Discussioncontrasting
confidence: 48%
“…Therefore, we suggest lactate monitoring during linezolid therapy within day 7. Elevation of serum lactate was more prevalent in patients with other comorbidities, [ 12 , 13 ] but in our study, such elevation also occurred in patients without comorbidities. Therefore, we suggest lactate monitoring for all patients, and not the at-risk group alone.…”
Section: Discussioncontrasting
confidence: 48%
“…One case–control study and several case reports, including a total of 7 patients, suggested an association between linezolid mitochondrial toxicity and the mitochondrial ribosomal RNA polymorphisms A2706G or G3010A ( Palenzuela, L, et al, 2005 , Carson, J, et al, 2007 , Velez, JC and Janech, MG, 2010 , Del Pozo, JL, et al, 2014 ). In our analysis, we did not find any association between mitochondrial toxicity adverse events and these or any other mitochondrial RNA polymorphism ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, other drugs may prevent ATP production (antibiotics such as oligomycin or local anaesthetic drugs), inhibit protein synthesis (antibiotics including chloramphenicol, tetracycline, erythromycin, eperezolid, linezolid and aminoglycosides) [ 19 , 58 ], decrease electron transfer (anticholesterolemics) or membrane potential, impair mitochondrial lipid metabolic pathways (barbiturates) or increase apoptosis (including benzodiazepines) [ 59 ]. Such mitochondrial disturbances have been reported to cause adverse effects including deafness [ 60 ], peripheral neuropathy [ 61 ], hyperlacatemia, lactic acidosis [ 62 ] and gastrointestinal, dermatological or hematological alterations, myopathic syndrome or gastrointestinal disturbances, among others [ 63 ]. Specific safety and mitochondrial toxic studies in human pregnancies are lacking for most of these drugs.…”
Section: Resultsmentioning
confidence: 99%